1998
DOI: 10.1055/s-2007-994068
|View full text |Cite
|
Sign up to set email alerts
|

Has The Outcome for Extremely Low Gestational Age (ELGA) Infants Improved Following Recent Advances in Neonatal Intensive Care?

Abstract: The objectives of this paper are to examine (a) the survival of extremely low-gestational-age (ELGA) infants born at 23-28 weeks' gestational age (GA) and (b) the neurodevelopmental outcome at 18 months corrected age for those born at 23-25 weeks' GA during 1991-1993, when antenatal steroids, surfactant, and dexamethasone for bronchopulmonary dysplasia had become accepted treatments; and to compare with an earlier (1983-1989), previously published large cohort (in a presurfactant era) from our institution. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 9 publications
1
52
2
Order By: Relevance
“…The deteriorated outcome was primarily caused by visual impairments, whereas the incidence of cerebral palsy remained constant. In studies from the 1990s, neonatal survival rates of infants born at 22 to 23 GWs varied from 0% to 25% 21,23,28 and was 9% in our study, which was significantly lower than that of the infants born at 24 to 25 GWs (60%). However, statistically significant differences in neonatal survival among GW groups at 25 to 29 GWs were not found.…”
Section: Figcontrasting
confidence: 76%
See 1 more Smart Citation
“…The deteriorated outcome was primarily caused by visual impairments, whereas the incidence of cerebral palsy remained constant. In studies from the 1990s, neonatal survival rates of infants born at 22 to 23 GWs varied from 0% to 25% 21,23,28 and was 9% in our study, which was significantly lower than that of the infants born at 24 to 25 GWs (60%). However, statistically significant differences in neonatal survival among GW groups at 25 to 29 GWs were not found.…”
Section: Figcontrasting
confidence: 76%
“…Besides of low survival rate, the infants born at 22 to 23 GWs also have poor outcome: long-term disability rates varied in previously mentioned studies from 67% to 100%. 21,23,28 In our study, no infant born at 22 to 23 GWs had completely normal short-term follow-up results.…”
Section: Figmentioning
confidence: 44%
“…Thus there is still a need for more research on how to improve neonatal care. The outcome of this type of research will be beneficial for all premature infants whether they are boys or girls [102].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding survival odds were obtained from the Vermont Oxford Network Quality Management Report for the most recent available year (2000). 5 Rates of major disability (Table 1) were derived from a comprehensive review of the published literature [6][7][8][9][10][11][12][13][14][15][16][17][18] that included cohorts from single referral centers 8,11,12,14,16 and from geographically defined regions. 6,7,9,10,13,15,17,18 We included only long-term outcome studies that reported data based on gestational age (information that is more useful in the context of prenatal counseling); reported follow-up data Ն18 months after the estimated date of delivery, with significant proportions of survivors assessed (11 studies had rates of 83-100% and 2 studies had rates of 54% and 73%); used validated tools for assessment; and had similar definitions for major disabilities, including mental retardation/neurodevelopmental delay, cerebral palsy, blindness, and deafness ( Table 1).…”
Section: Interventionmentioning
confidence: 99%
“…24,25 Outcome statistics are generally well received by prospective mothers of preterm infants during prenatal consultation. 3 According to published data, the chances of survival increase by 2% to 4% with each additional intrauterine day for gestations of 23 to 26 weeks, 5,15,26 and the majority of infants who survive are free of major disabilities. 27 There seems to be sufficient evidence now to establish the limit of viability in the United States at 23 weeks of gestation.…”
Section: E484mentioning
confidence: 99%